Operational Resilience and Business Continuity Management in Global Shipping Companies: Lessons from Supply Chain Disruptions and Environmental Regulatory Shifts - Abdul Rochman (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
Global shipping enterprises have confronted an unprecedented convergence of operational disruptions — pandemic-induced supply chain collapses, escalating port congestion, geopolitical trade disruptions, and accelerating environmental regulatory change — that have fundamentally exposed vulnerabilities in traditional business continuity frameworks designed for relatively predictable operational environments. This study investigates how global shipping companies develop, implement, and refine operational resilience and business continuity management (BCM) frameworks in response to multi-dimensional disruptions. Employing qualitative thematic analysis of in-depth interviews with thirty shipping industry executives, port operations managers, logistics professionals, and regulatory experts, the research identifies four resilience architecture dimensions and six critical business continuity capability domains that distinguish resilient from fragile maritime enterprises. Findings demonstrate that resilience in global shipping requires dynamic capability integration, multi-stakeholder collaboration, and adaptive regulatory management rather than static contingency planning. The study advances maritime business management scholarship by providing a theoretically grounded and empirically rich framework for operational resilience in complex maritime enterprise environments.